The Arab lobby : the invisible alliance that undermines America's interests in the Middle East - Bard, Mitchell Geoffrey, 1959- (New York : Harper, 2010)
"Critics claim that a nefarious Israel Lobby dictates U.S. policy in the Middle East. Yet the Arab Lobby in this country is older, richer, and more powerful than AIPAC"--
Keywords: Lobbying -- United States; Arab Americans -- Politics and government; United States -- Foreign relations -- Middle East; Middle East -- Foreign relations -- United States